2020
DOI: 10.32794/mr11250079
|View full text |Cite
|
Sign up to set email alerts
|

Low melatonin as a contributor to SARS-CoV-2 disease

Abstract: That the pineal gland is a source of melatonin is widely known; however, by comparison, few know of the much larger pool of extrapineal melatonin. That pool is widely distributed in all animals, including those that do not have a pineal gland, e.g., insects.  Extrapineal melatonin is not released into the blood but is used locally to function as an antioxidant, anti-inflammatory agent, etc. A major site of action of peripherally-produced melatonin is the mitochondria where it neutralizes reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 145 publications
(168 reference statements)
0
7
0
Order By: Relevance
“…The rationale for this is that the elevated free radical generation as well as the inflammatory response associated with this disease persists during both the light and dark period. To aid in the inhibition of these damaging responses, it may improve the clinical outcome if melatonin is used as a treatment of infected individuals during the day, when circulating melatonin levels are at their nadir [ 109 , 110 ].…”
Section: Effective Dose Timing Of Administration Limitations and Futu...mentioning
confidence: 99%
“…The rationale for this is that the elevated free radical generation as well as the inflammatory response associated with this disease persists during both the light and dark period. To aid in the inhibition of these damaging responses, it may improve the clinical outcome if melatonin is used as a treatment of infected individuals during the day, when circulating melatonin levels are at their nadir [ 109 , 110 ].…”
Section: Effective Dose Timing Of Administration Limitations and Futu...mentioning
confidence: 99%
“…Melatonin is a highly studied biomolecule due to its known role in mammals as a regulating hormone of sleep-wake cycles, and other functions in endogenous rhythms, mood, metabolism, and immunological responses [9,10]. In addition, it has been investigated as to its therapeutic efficacy in Alzheimer's disease, Parkinsonism, cancer, diabetes, and SARS-CoV-2 [11][12][13][14][15][16][17].…”
Section: Biosynthesis Of Melatonin In Plantsmentioning
confidence: 99%
“…Plants 2021, 10, x FOR PEER REVIEW 2 of 14 tions in endogenous rhythms, mood, metabolism, and immunological responses [9,10]. In addition, it has been investigated as to its therapeutic efficacy in Alzheimer's disease, Parkinsonism, cancer, diabetes, and SARS-CoV-2 [11][12][13][14][15][16][17].…”
Section: Biosynthesis Of Melatonin In Plantsmentioning
confidence: 99%
“…It has been observed that melatonin was only used in 11 clinical trials. The time spent on clinical trials, using a bioactive compound, such as melatonin, is not supported, due to the lack of protective patents for a natural compound ( 71 ). However, this obstacle has to be surpassed, not only due to its highly safe and effective profile, but also due to its multifactorial and synergic pharmacological actions ( 15 , 72 ).…”
Section: Clinical Trials Using Melatonin To Treat Covid-19mentioning
confidence: 99%